Splenic hematoma may present as large bowel obstruction: A case report. (2019) - Kolwitz, Christine; Esposito, Christopher; Gauvin, Caitlin; Gaduputi, Vinaya; Chiong, Brian; Sunkara, Tagore; Baltazar, Gerard A.
Highlights: Traumatic splenic hematoma may present as large bowel obstruction. Large bowel obstruction secondary to splenic hematoma may become a more-frequently recognized phenomenon. Large bowel obstruction secondary to splenic hematoma may be managed non-operatively and resolve in approximately one week. Abstract: Introduction: Large bowel obstruction (LBO) warrants prompt evaluation and management. Although causes of LBO are most commonly intrinsic to the colon (e.g. malignancy, diverticular stricture, intussusception or volvulus), rare extrinsic etiologies exist. An extremely rare extrinsic etiology of LBO described only once, is compressive splenic hematoma. Presentation of case: A 64-year-old female presented to the emergency department complaining of two days of diffuse abdominal pain and distension, watery diarrhea and nausea subsequent to a mechanical fall to her left side. Computed tomography demonstrated a grade 3 splenic hematoma with active extravasation, causing extrinsic compression and obstruction of the colon. Embolization of the splenic artery was performed, and non-operative LBO management resulted in resumption of normal bowel function after six days. Discussion: To our knowledge, the only other case of colonic compression by splenic hematoma (a case report in the radiology literature from 1994) describes a 62-year-old male whose symptoms similarly spontaneously resolved. Increasing frequency of non-operative management of splenic trauma may result in increased frequency of splenic hematoma complications. Physicians and surgeons who treat LBO should be aware of this rare etiology and its potential for non-operative management. Conclusion: Our case demonstrates the importance of considering splenic hematoma as an etiology of LBO, particularly in the setting of trauma and that management of this entity can be successfully non-operatively.